Pemeriksaan Jumlah Kapang Sebagai Indikator Kualitas Terasi Di Pasar Tambaksari Surabaya - Dita Artanti; Fitrotin Azizah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2019)
The main problem that occurs in the community is the lack of awareness of the importance of hygiene during the manufacture and storage of shrimp paste. This can trigger one of the contaminations originating from microorganisms including mold. The aimed of this study was to determine the number of molds as an indicator of shrimp paste quality in the Tambaksari market in Surabaya. This research is descriptive. The population of this research is shrimp paste traders in Tambaksari market in Surabaya. The research variable is the number of molds in the shrimp paste in the packaging without a brand in the Tambaksari market in Surabaya. Data on the number of molds was tabulated and analyzed descriptively by calculating the percentage of samples that were of good quality and not good. The results of the research on the number of mold colonies on shrimp paste sold in the Tambaksari market in Surabaya showed that the number of mold colonies in shrimp paste samples was safe to consumed because the amount was <2 x 102 colonies / gr, the average percentage of all shrimp paste samples was 100% good quality. The highest growth rate of mold colonies was 19 x 101 colonies / gr and the lowest growth rate of mold colonies was 0 x 101 colony / gr. Keywords : The Number of  Mold, Shrimp paste